Exploring the role of healthcare management in improving patient adherence to end- stage renal disease treatment - the case of Pietersburg Renal Dialysis Unit - Thema, Momotho Georgina (Stellenbosch : Stellenbosch University, 2024)
Thesis (MPA)--Stellenbosch University, 2024.